ISLAMIC SOCIAL FINANCE AND MACROECONOMIC DYNAMICS: UNVEILING CONNECTIONS THROUGH TIME SERIES ANALYSIS - Rahayu, Eluvia Nanda; Pimada, Laila Masruro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
There are 87 percent of Muslims in Indonesia who provide high zakat potential. This is evidenced by the collection and distribution of zakat which has always experienced significant growth over the past decade. Zakat distribution program for mustahik was formed to help mustahik daily life such as distribution of the economic, education, health, humanitarian and da'wah sectors. However, the existing reality explains that distribution of zakat has not yet supported economic. growth, poverty reduction, and human development over the past decade. Given this phenomenon, this study aims to examine the effect of zakat on economic growth, poverty, and human development in the short and long term in 2011-2022. This research was conducted using Vector Error Correction Model (VECM) method with 48 samples. The estimation results from this study state that the distribution of zakat has a significant effect on economic growth, poverty, and human development in the short and long term. Based on the estimation results, this research contributes in the form of policy advice on the distribution and utilization of zakat in Indonesia.